2018
DOI: 10.1038/s41427-018-0095-5
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-based quasi-solid-state lithium–oxygen batteries with high energy efficiency and a long cycling lifetime

Abstract: An aprotic lithium-oxygen battery with an ultrahigh theoretical energy density has attracted significant attention as the next-generation electrochemical energy device demanded by all-electric vehicles and other high-energy devices. Extensive effort has recently been devoted to improving the performances of cathodes, anodes, and electrolytes. However, as an integrated system, the overall battery properties are not determined by the individual components but by the synergy of all components. Despite important p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 32 publications
1
39
0
Order By: Relevance
“…[105][106][107][108][109] Pore generation is often used in the electrochemical research fields in order to increase the surface area of the electrodes. [110][111][112][113][114] Porous structures of CVDgraphene films were fabricated with porous Ni foils, originated from de-alloyed Ni-Mn foils. [68] These kinds of structural transformations of planar graphene to form a large surface area without deteriorating the flexibility have been evaluated as suitable for fabricating high-performance flexible battery electrodes.…”
Section: Cvd-graphenementioning
confidence: 99%
See 1 more Smart Citation
“…[105][106][107][108][109] Pore generation is often used in the electrochemical research fields in order to increase the surface area of the electrodes. [110][111][112][113][114] Porous structures of CVDgraphene films were fabricated with porous Ni foils, originated from de-alloyed Ni-Mn foils. [68] These kinds of structural transformations of planar graphene to form a large surface area without deteriorating the flexibility have been evaluated as suitable for fabricating high-performance flexible battery electrodes.…”
Section: Cvd-graphenementioning
confidence: 99%
“…CVD process with de-alloyed NiMn foils N-doped graphene Flexible in batteries [114] Graphene foams (for LIBs) CVD process with Ni foams Graphene foam Flexible in batteries (radius of 5 mm) [71] Graphene foams with sulfur loading (for LSBs) CVD process with…”
Section: Ni Foilmentioning
confidence: 99%
“… 23 For example, Chen et al reported a porous graphene/Li anode by infusing molten Li into a free-standing, bicontinuous porous N-doped graphene scaffold ( Figure 3 b). 13 This composite anode can simultaneously resolve the dendrite growth and pulverization of Li metal anode, as a result, significantly boosting the cycling stability of Li–O 2 batteries. However, it should be noted that the introduction of the 3D host will undoubtedly decrease the energy density of the Li–O 2 batteries, whereas the high surface area increases the possibility of Li metal involved side reactions.…”
Section: Protection Strategies For LI Metal Anodesmentioning
confidence: 99%
“…As a routine quasi-solid-state electrolyte, gel polymer electrolyte (GPE) with low cost and moderate Li + conductivity has been demonstrated effective in reducing side reactions, suppressing dendrite growth, and inhibiting RMs induced shuttle attack in the Li metal anode, enabling its stable operation in Li–O 2 batteries. 13 Although these positive effects, the GPE with a limited amount of liquid electrolyte still suffers from the issues of low Young’s modulus, volatilization, and less efficient O 2 blockage. As a result, solid-state electrolyte (SSE) stands out owing to its unique advantages of relative high Young’s modulus, nonvolatility, as well as the only Li + transportation ability that fully isolates the crossover of undesirable components.…”
Section: Protection Strategies For LI Metal Anodesmentioning
confidence: 99%
See 1 more Smart Citation